MCAT general chemistry review - Kaplan, Inc.; Scientific American, inc. (2010)
"Comprehensive review, practice, and strategies" -- Cover.
Includes index.
Some volumes issued in container with title: MCAT complete 5-book subject review.
Volume copyrighted 2015 misnumbered as: 2nd edition (i.e., earlier 2012 volume numbered 3rd edition).
Volume for 2015 issued in partnership with Scientific American.
Keywords: Medical College Admission Test -- Study guides -- Periodicals; Medical colleges -- United States -- Entrance examinations -- Study guides -- Periodicals; Chemistry -- Examinations -- Study guides -- Periodicals; Chemistry -- Examinations; Medical College Admission Test; Medical colleges -- Entrance examinations; United States; Examinations; Periodicals; Study guides; Examinations; Study guides